2009
DOI: 10.1073/pnas.0905083106
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Drosophila insulin-like peptides causes growth defects and metabolic abnormalities

Abstract: Insulin/Insulin-like growth factor signaling regulates homeostasis and growth in mammals, and is implicated in diseases from diabetes to cancer. In Drosophila melanogaster, as in other invertebrates, multiple Insulin-Like Peptides (DILPs) are encoded by a family of related genes. To assess DILPs' physiological roles, we generated small deficiencies that uncover single or multiple dilps, generating genetic loss-of-function mutations. Deletion of dilps1-5 generated homozygotes that are small, severely growth-del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
168
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(172 citation statements)
references
References 49 publications
(82 reference statements)
4
168
0
Order By: Relevance
“…These genotypes may therefore influence caste by restricting the size range, with workerbiased genotypes producing individuals whose growth is stunted, and queen-biased genotypes producing individuals that are starvation intolerant (and therefore either attain large size or die). Both types of genotypic effects on size have been observed in Drosophila melanogaster (Kramer et al, 2008;Zhang et al, 2009).…”
Section: Caste Determination Determining Adult Sizementioning
confidence: 98%
“…These genotypes may therefore influence caste by restricting the size range, with workerbiased genotypes producing individuals whose growth is stunted, and queen-biased genotypes producing individuals that are starvation intolerant (and therefore either attain large size or die). Both types of genotypic effects on size have been observed in Drosophila melanogaster (Kramer et al, 2008;Zhang et al, 2009).…”
Section: Caste Determination Determining Adult Sizementioning
confidence: 98%
“…28) Of Drosophila, it has been frequently reported that mutant alleles involved in the IIS/TOR pathway, such as dilp (s), 29) InR, 30) and TOR, 31) also cause developmental defects and delays. In addition, TOR activity is required by the prothoracic gland (PG), which secretes the molting hormone ecdysone, while activation of TOR solely in PG cells reverses the developmental delay caused by nutritional restriction.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, the neurons that express some of these ILPs send or receive projections from subesophageal ganglion interneurons, which in turn receive information (Melcher and Pankratz, 2005;Rulifson et al, 2002;Yang et al, 2008) from gustatory neurons that innervate chemosensory structures within the fly mouthparts (Scott et al, 2001). In addition, some of these neuronally expressed ILPs (dilp2, dilp3 and dilp5) have been proposed to regulate growth and metabolism in a nutrient leveldependent manner, whereas others do not (Broughton et al, 2008;Grönke et al, 2010;Ikeya et al, 2002;Min et al, 2008;Zhang et al, 2009). Some are also required in other processes, such as in selecting an optimal environment for egg laying, which is dilp7 dependent (Yang et al, 2008).…”
Section: The Relevance Of Multiple Ilps In Other Animalsmentioning
confidence: 99%